1993
DOI: 10.1143/jjap.32.1787
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Desorption and Infrared Studies of Plasma-Enhanced Chemical Vapor Deposited SiO Films with Tetraethylorthosilicate

Abstract: Thermal desorption and Fourier transform infrared spectroscopies were used to study plasma-enhanced chemical vapor deposited SiO films from tetraethylorthosilicate. Significant water desorption and concomitant structural changes were observed for the films during subsequent heat treatments between 100 and 700°C. The films exhibited three distinct water desorption states. The desorption temperatures were approximately 100-200°C for the first state, 150-300°C for the second state, and 350-650°C for the third sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
63
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(65 citation statements)
references
References 10 publications
2
63
0
Order By: Relevance
“…Figure 8 shows examples of (a) a nonsymmetrical TPD curve indicated by the solid line (the first-order reaction) and (b) a symmetrical TPD curve indicated by the dashed line (the second-order reaction) as a function of temperature. The arrow on the nonsymmetrical TPD curve corresponds to the evolution of physisorbed and chemisorbed H 2 O, which is specified to be a liquid such as water and water molecules hydrogen-bonded to Si-OH bonds at nanopore sites in the films (Hirashita et al, 1993).…”
Section: Wwwintechopencommentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 8 shows examples of (a) a nonsymmetrical TPD curve indicated by the solid line (the first-order reaction) and (b) a symmetrical TPD curve indicated by the dashed line (the second-order reaction) as a function of temperature. The arrow on the nonsymmetrical TPD curve corresponds to the evolution of physisorbed and chemisorbed H 2 O, which is specified to be a liquid such as water and water molecules hydrogen-bonded to Si-OH bonds at nanopore sites in the films (Hirashita et al, 1993).…”
Section: Wwwintechopencommentioning
confidence: 99%
“…For chemical-vapor-deposited SiO 2 films, three distinct H 2 O desorption states have been defined (Hirashita et al, 1993). They are physisorbed H 2 O evolved at temperatures between 100 and 200 °C and chemisorbed H 2 O evolved at temperatures between 150 and 300 °C in a TPD measurement.…”
Section: Wwwintechopencommentioning
confidence: 99%
See 1 more Smart Citation
“…1. [36][37][38][39] The morphology of the samples was observed using a scanning electron microscope (SEM, KEYENCE VE-8800) with an accelerating voltage of 20 kV. The X-ray diffraction (XRD) data at room temperature were taken for all samples using CuK¡ radiation.…”
Section: Methodsmentioning
confidence: 99%
“…21) The structural properties of silica films prepared by chemical vapor deposi tion (CVD) and solgel techniques have been investigated by TPD. 22)30) These studies revealed that the silica films con tained different organic components depending on the fabri cation processes and starting materials used such as tetra ethoxysilane. The results also suggest that TPD can be applied to analyze the formation processes of solgelderived metal oxide films.…”
Section: )17)mentioning
confidence: 99%